STUDI ANALISIS TERHADAP PENGGUNAAN TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHIQUE (SEFT) YANG DAPAT DIGUNAKAN SEBAGAI TERAPI PADA KLIEN YANG MENGALAMI POST TRAUMATIC STRESS DISORDER (PTSD) - Lilyanti, Henny (STIKes BTH Tasikmalaya, 2016)
The experience of being victims or perpetrators or witnesses of traumatic experience can cause physical and emotional disorder (psychological) when this disorder lasted more than 4 weeks post trauma and diagnosed as Post Traumatic Stress Disorder (PTSD). Traumatic experience makes the life of the victim experiencing a decrease in quality of life due to having a lot of physical disorders such as shortness of breath, dizziness, loss of appetite, impaired cognitive form of daze, unable to forget, impaired concentration, emotions in the form of hallucinations, nightmares, irritability, impaired social and behavioral disorders (Varcarolis, 2006). A person categorized as sufferers of PTSD or traumatic incident suffered casualties when already experiencing disruption of emotions. This scientific masterpiece using descriptive method in the form of a literature study traced via Google Scholar, proquest and there are 13 articles accordingly.Therapy can be used as alternative SEFT psychotherapy to address emotions in people with PTSD or misbehaving emotion because of the traumatic experience. This therapy is a new method from EFT that have proved effective in the case of Viet Nam war veteran PTSD but this therapy is more effective because it included elements of spirituality. The principle of this therapy is to balance the body's energy in the 18-point energy meridians so that when the energy of the body back in balance then the negative emotions will disappear (Zainuddin, 2007). Therapy effective for addressing PTSD SEFT or emotional disorders who experience a traumatic experience because of this therapy because it is easy and relatively fast with high effectiveness